2007
DOI: 10.1177/183335830703600204
|View full text |Cite
|
Sign up to set email alerts
|

ICD-10 Mortality Coding and the NEIS: A Comparative Study

Abstract: The collection and utilisation of mortality data are often hindered by limited access to contextual details of the circumstances surrounding fatal incidents. The National Coroners Information System (NCIS) can provide researchers with access to such information. The NCIS search capabilities have been enhanced by the inclusion of data supplied by the Australian Bureau of Statistics (ABS), specifically the ICD-10 Cause of Death code set. A comparative study was conducted to identify consistencies and differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 3 publications
2
36
1
Order By: Relevance
“…Analysis illustrated that independently assigned external cause ICD-10 UCoD codes matched exactly with the ABS assigned codes in 4,397 (70.8%) deaths. The proportion of exact matches for external cause deaths for this study was higher than reported in a previous study (Daking & Dodds 2007), which compared a smaller subset of national data to the 4 th character level. A further 1,293 deaths (20.8%) matched on intent and external cause category but not specificity, 285 (4.6%) on external cause category and specificity but not intent and 190 (3.1%) matched on intent but not external cause category.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Analysis illustrated that independently assigned external cause ICD-10 UCoD codes matched exactly with the ABS assigned codes in 4,397 (70.8%) deaths. The proportion of exact matches for external cause deaths for this study was higher than reported in a previous study (Daking & Dodds 2007), which compared a smaller subset of national data to the 4 th character level. A further 1,293 deaths (20.8%) matched on intent and external cause category but not specificity, 285 (4.6%) on external cause category and specificity but not intent and 190 (3.1%) matched on intent but not external cause category.…”
Section: Discussioncontrasting
confidence: 72%
“…These codes can be used as the primary variable for case identification and/or to validate other case identification methods. Previous studies have shown discrepancies between the ICD-10 codes assigned by the ABS in the NCIS and an independent recode (Daking & Dodds 2007) and between the classification of the NCIS variable Intent -completion (Elnour & Harrison 2009). …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Victorian Institute of Forensic Medicine houses the NCIS and operates a quality assurance programme designed to identify and amend coding errors and to ensure consistent coding across jurisdictions (National Coroners Information System, 2011). Examinations of the quality of the NCIS data suggest it reliably captures information on deaths reportable to coroners (Daking and Dodds, 2007;Driscoll et al, 2003).…”
Section: Datamentioning
confidence: 98%
“…17 Examinations of the quality of the data in the NCIS suggest that it reliably captures information on reportable deaths. 18,19 This study was approved by the ethics committee at the Department of Justice, Victoria, Australia.…”
Section: Datamentioning
confidence: 99%